PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS DI KELAS V SDN 063 KEBON GEDANG - Tasya Wulandari (Jurnal Riset Multidisiplin Edukasi, 2026)
This research is motivated by the low critical thinking skills of students in Science and Social Studies (IPAS) subjects at the elementary school level. The purpose of this study was to determine the effect of using the Scramble learning model on the critical thinking skills of fifth-grade students at SDN 063 Kebon Gedang. The research method used was a quasi-experimental method with a Non-equivalent Control Group Design. The research sample consisted of two classes: an experimental class using the Scramble model and a control class using the Problem Based Learning (PBL) model. Data collection techniques utilized critical thinking skills tests in the form of essay questions. The results of the prerequisite analysis test showed that the data were normally distributed based on the Shapiro-Wilk test and had homogeneous variance based on Levene's test. Based on the results of the hypothesis testing using the Independent Sample t-test, a significance value (2-tailed) of 0.000 < 0.05 was obtained, resulting in the rejection of h_o and the acceptance of h_a. This indicates a significant difference in critical thinking skills between the experimental class and the control class. Furthermore, the effect size test results showed a value of 2.44, which falls into the "very large effect" category. Thus, it can be concluded that the Scramble learning model has a significant influence and provides a strong impact on improving students' critical thinking skills in IPAS learning.